2021
DOI: 10.1186/s12989-021-00433-y
|View full text |Cite
|
Sign up to set email alerts
|

Silica-coated magnetic-nanoparticle-induced cytotoxicity is reduced in microglia by glutathione and citrate identified using integrated omics

Abstract: Background Nanoparticles have been utilized in brain research and therapeutics, including imaging, diagnosis, and drug delivery, owing to their versatile properties compared to bulk materials. However, exposure to nanoparticles leads to their accumulation in the brain, but drug development to counteract this nanotoxicity remains challenging. To date, concerns have risen about the potential toxicity to the brain associated with nanoparticles exposure via penetration of the brain blood barrier to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(65 citation statements)
references
References 128 publications
4
61
0
Order By: Relevance
“…Recently, it has been suggested that glutathione and citrate attenuate cytotoxicity induced by urban PM in microglia [ 198 ]. The combination of glutathione and citrate reduces the toxicity of PM exposed to cells through mechanisms such as ROS scavenging, organic acid supplementation in the tricarboxylic acid cycle, and chelating Ca 2+ ions.…”
Section: Strategies To Mitigate the Effects Of Pm 25 ...mentioning
confidence: 99%
“…Recently, it has been suggested that glutathione and citrate attenuate cytotoxicity induced by urban PM in microglia [ 198 ]. The combination of glutathione and citrate reduces the toxicity of PM exposed to cells through mechanisms such as ROS scavenging, organic acid supplementation in the tricarboxylic acid cycle, and chelating Ca 2+ ions.…”
Section: Strategies To Mitigate the Effects Of Pm 25 ...mentioning
confidence: 99%
“…To compensate for the weakness of metabolomics, integration of omics technologies is highly recommended, but the development of this strategy is challenging [102]. Integrated omics studies have identified novel biological changes underlying various conditions in vitro [18,85,[103][104][105][106][107]. There have been limitations in the analysis of other omics data, except for metabolites, from CSF samples due to technical issues.…”
Section: Integrated Omicsmentioning
confidence: 99%
“…Machine learning is used for handling large-scale datasets, including integrated omics data [105]. Machine learning is divided into supervised learning, unsupervised learning, and reinforcement learning [55,110].…”
Section: Integrated Omicsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, integration of transcriptomics and metabolomics, namely metabotranscriptomics, demonstrated novel cellular responses and in-depth toxicological intracellular pathways associated with NPs of MNPs@SiO 2 (RITC) [ 29 , 30 , 31 , 32 , 33 , 34 ]. In addition, artificial intelligence (AI) approaches, such as machine learning, have been applied to classify the integration of omics data and predict nanotoxicity, which are massive and heterogeneous for generating a single network with integrated transcriptomics, proteomics, and metabolomics [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%